A skin burn associated with Ranunculus arvensis (wedding bloom) - Orak Murat; Ustundag Mehmet; Guloglu Cahfer; Tas Mahmut; Baylan Berat (Wolters Kluwer Medknow Publications, 2009)
Ranunculus arvensis L-a member of Ranunculaceae family- is grown as a wild plant in productive agriculture lands of the altitude between 1 to 1850 m mainly in the Mediterranean Region and Iran-Turan vegetation in Turkey. Skin burn cases associated with Ranunculaceae family is very limited in literature and according to the authors′ knowledge this is the only report in literature from Turkey. In this report, we have presented a case of skin burn associated with Ranunculus arvensis represented to our emergency service.